Boosting energy metabolism and biosynthesis in diverse organisms by a common bacterial salvage lipoylation protein - Runqing Yang; Yingying Wang; Minghua Kong; Zhijuan Hu; Zhe Zhang; Kun Shen; Jiali Meng; An-Ping Zeng (Nature Communications)
Abstract Lipoylation is a highly conserved post-translational modification (PTM) crucial for energy metabolism enzymes, with distinct pathways across organisms. Whereas bacteria like Escherichia coli inherit both salvage and de novo pathways, only the latter is found in eukaryotes. Here, we present a PTM-based strategy that achieves multiple metabolic benefits with a single intervention. By expressing E. coli-derived lipoate protein ligase A (LplA) from the salvage pathway, we enhance lipoylation and the activities of the pyruvate dehydrogenase, alpha-ketoglutarate dehydrogenase complexes and glycine cleavage system in mammalian, algal and fungal cells, leading to improved energy metabolism, cofactor supply, mitochondrial function, and overall cell physiology. Our approach specifically targets multiple metabolic hubs through PTM modulation. Beyond its fundamental significance, our finding presents a unified and efficient way to boost biosynthesis across organisms, demonstrated in antibody production in Chinese hamster ovary cells, fatty acids synthesis in cyanobacteria and diatoms, and organic acid production in fungi.